2009
DOI: 10.1007/s10964-009-9406-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Trajectories of Adolescents’ Depressive Phenomena: An Examination of Early Risk Factors

Abstract: Few studies have examined risk factors of childhood and early adolescent depressive symptomatology trajectories. This study examined self-report depressive symptomatology across a 6-year time period from 2nd to 8th grade to identify latent groups of individuals with similar patterns of depressive phenomena in a sample of 951 children (440 girls, 511 boys). Analyses, using semiparametric group modeling (SGM), identified 5 trajectory groups for girls and boys: low depressed stables, low depressed risers, mildly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
6
40
0
2
Order By: Relevance
“…according to our study, one of the key variables to take into consideration when selecting schools for mental health promotion programming in saskatoon health region is material deprivation. also, since depression was more common among girls than boys in our study, a finding that has been validated in many other studies (afifi, enns, cox, & Martens, 2005;Garber, 2006;Mazza, fleming, abbott, haggerty, & catalano, 2010), gender considerations should also be a component of programming. interactions between overweight/obese status and gender, along with bullying and gender, are further potential considerations when aiming to prevent depression.…”
Section: Discussionsupporting
confidence: 87%
“…according to our study, one of the key variables to take into consideration when selecting schools for mental health promotion programming in saskatoon health region is material deprivation. also, since depression was more common among girls than boys in our study, a finding that has been validated in many other studies (afifi, enns, cox, & Martens, 2005;Garber, 2006;Mazza, fleming, abbott, haggerty, & catalano, 2010), gender considerations should also be a component of programming. interactions between overweight/obese status and gender, along with bullying and gender, are further potential considerations when aiming to prevent depression.…”
Section: Discussionsupporting
confidence: 87%
“…Mixture models also all allow "direct" and "indirect" interpretations of latent classes. Under the "direct" interpretation, extracted classes are hypothesized to correspond with unobserved population subgroups (e.g., Mazza, Fleming, Abbott, Haggerty, & Catalano, 2010). Under an "indirect" interpretation, classes can be used to discretely approximate unknown distributional forms even without the assumption that population subgroups exist (e.g., Bauer, 2005;Nagin, 2005).…”
mentioning
confidence: 99%
“…Prior research on mental health trajectories in elementary school children suggests that emotional well-being, as indicated by depressive symptomatology, tends to stay stable or decline across time (Mazza et al 2010). Analogous longitudinal studies on indicators of SWB among children are lacking, but a similar trend is suggested by cross-sectional research with adolescents that revealed a decreasing trend for life satisfaction, which was highest among the youngest children surveyed (age 11) and progressively lower for 12 year olds and then each age group through the oldest youth sampled (age 16; Goldbeck et al 2007).…”
Section: Limitations Of Pilot Study and Recommendations For Future Rementioning
confidence: 99%